Whole-body vibration exposure characterization in bus drivers of Haikou City: A comparison between two health risk assessment methods - Yun CHEN; Longyi WANG; Zhongxu WANG; Ning JIA; Qingsong CHEN (环境与职业医学, 2023)
BackgroundLong-term exposure to whole-body vibration (WBV) will affect the health of occupational drivers. However, research on the characteristics of WBV exposure by urban bus drivers and health risk evaluation is still insufficient. ObjectiveTo identify the characteristics of occupational WBV exposure of bus drivers serving 31 bus routes provided by three branches of Haikou Public Transport Group, and to evaluate their occupational health risks related to WBV. MethodsA total of 31 out of 142 bus routes run by three branches of Haikou Public Transport Group were selected to monitor WBV exposure of 31 bus drivers during driving. WBV parameters such as triaxial frequency weighted acceleration (awx, awy, awz) and triaxial crest factor (CFx, CFy, CFz) of the drivers were determined with a six-channel human vibration meter. Two methods, 8-hour daily value of the weighted root mean square average weighted vibration [A(8)] based on aw and 8-hour daily value of vibration dose [VDV(8)] based on vibration dose value (VDV), were used for health risk assessment and classified WBV health risk results into three levels (high, medium, and low) by the exposure action value (EAV) and exposure limit values (ELV) for A(8) and VDV(8) recommended by ISO 2631-1:1997. The two evaluation methods, A(8) and VDV(8), were compared by Fisher's exact test. ResultsRegarding the WBV parameters, the vector sum of acceleration (av) was 0.321-0.680 m·s−2, the VDV of monitoring interval was 3.824-10.174 m·s−1.75, and the VDV(8) was 6.039-13.505 m·s−1.75; their values in mean ± standard deviation were (0.480±0.100) m·s−2, (6.987±2.737) m·s−1.75, and (9.773±4.540) m·s−1.75, respectively. Positive correlations were found between awx and awz, av and awz, CFx and CFy, CFy and CFz. No bus route's WBV exposure level was graded as high health risk by either A(8) or VDV(8). The number of routes graded as low health risk by A(8) was 26, while the number by VDV(8) was 12. The consistency rates of health risk levels evaluated by the two methods were 66.7% (6/9), 54.6% (6/11), and 45.5% (5/11) for the three bus group branches, respectively. The difference in WBV health risk assessment results between the two evaluation methods was not statistically significant. ConclusionPositive correlations are found between triaxial acceleration and triaxial crest factor. There is no difference in the results of using A(8) and VDV(8) to evaluate health risks of WBV in urban bus routes.